Front Cover: Resonant Oscillations of Josephson Current in Nb‐Bi2Te2.3Se0.7‐Nb Junctions (Adv. Quantum Technol. 3/2022). Issue 3 (8th March 2022) - Stolyarov, Vasily S.; Roditchev, Dimitri; Gurtovoi, Vladimir L.; Kozlov, Sergey N.; Yakovlev, Dmitriy S.; Skryabina, Olga V.; Vinokur, Valerii M.; Golubov, Alexander A.
Abstract : In article number 2100124, Vasily S. Stolyarov and colleagues have observed unexpectedly fine (≈1 Oe) resonant oscillations of the critical Josephson current in the magnetic field in ballistic Nb‐Bi2 Te2.3 Se0.7 ‐Nb proximity junctions at temperatures below 500 mK. The peaked maxima of oscillations are attributed to the resonant transmission of quasiparticles through low‐lying Andreev bound states forming at the superconductor‐topological insulator interfaces owing to the p ‐wave component of the induced superconducting order.